A laboratory study of local scour beneath submarine pipelines in a wave-current interacted flow - 285506 Faridah Jaffar Sidek; Abdul Aziz Ibrahim, 1953-; International Offshore and Polar Engineering Conference (3rd : 1993 : Singapore)
07